Ticagrelor effects on myocardial infarction and the impact of event adjudication in the PLATO (Platelet Inhibition and Patient Outcomes) trial - Mahaffey, Kenneth; Held, Claes; Wojdyla, Daniel M.; James, Stefan K.; Katus, Hugo; Husted, Steen; Steg, Philippe Gabriel; Cannon, Christopher P.; Becker, Richard C.; Storey, Robert F.; Khurmi, Nardev S.; Nicolau, José C.; et al. (Journal of the American College of Cardiology, 2014)
This study sought to report the treatment effect of ticagrelor on myocardial infarction (MI) and the strategy for and impact of event adjudication in the PLATO (Platelet Inhibition and Patient Outcomes) trial. - Background - In PLATO, ticagrelor reduced cardiovascular death, MI, or stroke in patients with acute coronary syndromes (ACS).
Gesehen am 26.08.2020